2012
DOI: 10.1158/0008-5472.can-11-4216
|View full text |Cite
|
Sign up to set email alerts
|

LIGHT Delivery to Tumors by Mesenchymal Stem Cells Mobilizes an Effective Antitumor Immune Response

Abstract: Bone marrow-derived mesenchymal stem cells (MSC) have been shown to home into tumor tissues, where they promote tumor growth and suppress immune rejection. In this study, we tested whether MSCs engineered to express the immune stimulating factor LIGHT, a member of the TNF superfamily, could induce tumor regression. Using in vitro and in vivo migration assays, we found that LIGHT-expressing MSCs (MSC-L) displayed a strong tropism for tumor tissues. MSC-L treatment activated the LIGHT-signaling pathway, effectiv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 53 publications
1
31
0
Order By: Relevance
“…In vitro and in vivo MSCs migration assays were performed as previously reported (20). In brief, 5 Â 10 5 MSCs were incubated in serum-free medium for 48 hours and the resulting conditioned media were used as chemoattractants.…”
Section: In Vitro and In Vivo Msc Migration Assaymentioning
confidence: 99%
“…In vitro and in vivo MSCs migration assays were performed as previously reported (20). In brief, 5 Â 10 5 MSCs were incubated in serum-free medium for 48 hours and the resulting conditioned media were used as chemoattractants.…”
Section: In Vitro and In Vivo Msc Migration Assaymentioning
confidence: 99%
“…50 Furthermore, several studies have demonstrated MSC tropism on tumors, and our recent work also proved that MSCs can recruit macrophages and promote tumor growth. 24,51,52 Emerging evidence supports the idea that induction of mutations in stromal cells can promote tumor formation. Genetic mutations in stromal cells have been reported in breast cancer.…”
Section: Discussionmentioning
confidence: 90%
“…These include modification to produce immunostimulatory cytokines (e.g. IFN-α, IFN-β, IL-12) and T cell trafficking molecules such as LIGHT [50][51][52][53].…”
Section: Strategies To Counteract Adaptive Resistance To Immune Checkmentioning
confidence: 99%